Species diversity of bats (Chiroptera) in the Ukrainian Azov Region and features of their residence by seasons - Anatoliy Volokh; Petro Gorlov; Valeriy Siokhin; Igor Polishchuk (Theriologia Ukrainica, 2021)
The article presents the results of regional surveys of bats in 2010–2020 in places planned for the construction of wind farms. With the use of modern ultrasonic detectors, computer programs and an electronic library of voices, 15 species were found in the Ukrainian Azov Region. Their highest diversity (11–13 species) was revealed in places of intensive migration. First of all, these are the sites Armyansk, Chaplynka, and Askania-Nova, which are located between the Dnieper valley and the Crimean Peninsula. Probably, in this area, bats migrating from the northern and north-eastern regions cross the land and join those moving along the Azov coast. The movement of a significant number of animals is noticeable in the west of the Molochna River. A relatively large variety of bats occurs near the sites Botiyevo, Orlivka, and Primorsk, located directly on the northern shore of the Sea of Azov, along which the migratory movements of bats are particularly strong. During winter, with limited research in this period, 8 species were found, whereas 13 species during spring and autumn migrations and 11 species in summer. The almost complete transformation of the steppe into agrocoenoses bordered by forest belts and irrigation canals undoubtedly affected bats in addition to global warming. In recent years, in all places of the Ukrainian Azov Region, there has been a decline in the number of the common pipistrelle (Pipistrellus pipistrellus) and serotine bats (Eptesicus serotinus), and an increase in the abundance of the noctule bat (Nyctalus noctula), Kuhl's pipistrelle (Pipistrellus kuhlii), Nathusius' pipistrelle (Pipistrellus nathusii), and parti-coloured bat (Vespertilio murinus). In all seasons, the least common species were the brown long-eared bat (Plecotus auritus), Daubenton's bat (Myotis daubentonii), greater noctule (Nyctalus lasiopterus), lesser noctule (Nyctalus leisleri), Savi's pipistrelle (Hypsugo savii), and western barbastelle (Barbastella barbastellus).